Income and Household Consumption Uncertainty After the COVID-19 Pandemic Crisis: The Moderating Role of Financial Attention and Liquid Wealth Evidence from Indonesia - Resky Khaerunnisa; Goso Goso; Jumawan Jasman (Jurnal Simki Economic, 2026)
This study analyzes the impact of income uncertainty on household consumption in Indonesia after the COVID-19 pandemic, emphasizing the moderating roles of financial attention and liquid wealth. Using a quantitative design, we examine secondary data from official Indonesian sources for 2022 to 2024 through multiple regression and Moderated Regression Analysis. The results indicate that income uncertainty significantly reduces household consumption (β = -1.872, p < 0.01). Financial attention (β = 0.456, p < 0.05) and liquid wealth (β = 0.512, p < 0.05) significantly moderate this relationship by weakening the negative effect of uncertainty. Households with higher financial attention and greater liquid assets show stronger consumption resilience. These findings underline the need to strengthen financial literacy and expand access to liquid financial instruments. The study extends Precautionary Saving Theory by integrating behavioral and structural moderators in an emerging market crisis context.